ISLAM AWAL, RIDDAH, DAN PRAKSIS KEBEBASAN BERAGAMA: REINTERPRETASI HADIS MAN BADDAL DÃNAH FAQTULÃH - Ansor, Muhammad (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2015)
A doctrine that is associated to the Prophet for killing apostates was widely known by Muslim community, in spite of one of the main principles of the Islamic doctrines teached the freedom of religion. The following article discusses some Hadiths on killing apostates and relates them with the early Islamic historical narration. Besides, this article describes the classical and contemporary ulamas in their multiple understanding of Hadiths on killing apostates. Finally, I argue that the reasons of fighting against persons who are suspected as apostasy in the early Islamic period are more political in nature. Essentially, Islam allows people to convert to and from Islam, in the absence of criminal punishment under a sentence of death.